Emily Dickinson (Bloom's biocritiques, 2003)
With their unique combination of biography and criticism, these books serve as an excellent introduction to both the life and works of the world's literary masters. Spanning the canon, this series covers those writers most often taught in schools and provides in-depth knowledge.